2023
DOI: 10.1161/circulationaha.122.061288
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Association of Daily Steps With Cardiovascular Disease: A Harmonized Meta-Analysis

Abstract: BACKGROUND: Taking fewer than the widely promoted “10 000 steps per day” has recently been associated with lower risk of all-cause mortality. The relationship of steps and cardiovascular disease (CVD) risk remains poorly described. A meta-analysis examining the dose–response relationship between steps per day and CVD can help inform clinical and public health guidelines. METHODS: Eight prospective studies (20 152 adults [ie, ≥18 years of age]) were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 41 publications
2
27
1
1
Order By: Relevance
“…105 In addition, a recent harmonized meta-analysis found older adults (≥60 years) who walked 6000 to 9000 steps per day had a 40% to 50% lower CVD risk, including heart attack, compared to those who walked <2000 steps per day. 142 Similar findings are seen in the CHS (Cardiovascular Health Study), which found among 4207 older adults (mean age, 73 years) those who walked at least 49 blocks per week had a 36% to 47% lower risk of CHD, stroke, and CVD compared with those who walked <5 blocks per week. 143 These cohort studies highlight that engaging in any intensity of physical activity or taking more steps is related to better cardiovascular health in older adults.…”
Section: Older Adulthood (≥65 Years)supporting
confidence: 76%
See 1 more Smart Citation
“…105 In addition, a recent harmonized meta-analysis found older adults (≥60 years) who walked 6000 to 9000 steps per day had a 40% to 50% lower CVD risk, including heart attack, compared to those who walked <2000 steps per day. 142 Similar findings are seen in the CHS (Cardiovascular Health Study), which found among 4207 older adults (mean age, 73 years) those who walked at least 49 blocks per week had a 36% to 47% lower risk of CHD, stroke, and CVD compared with those who walked <5 blocks per week. 143 These cohort studies highlight that engaging in any intensity of physical activity or taking more steps is related to better cardiovascular health in older adults.…”
Section: Older Adulthood (≥65 Years)supporting
confidence: 76%
“…However, given inconsistencies in physical activity assessment tools used by these studies, additional methodological work is needed to harmonize and pool data to fully reflect physical activity changes across the adult lifecourse, such as the Steps for Health Collaborative. 142,152 Another data harmonization example is the International Children's Accelerometry Database which has pooled and harmonized over 37 000 raw accelerometer data files of children and adolescents aged 3 to 18 years from 20 studies worldwide (Europe, United States, Brazil, Australia). 153 However, there is a paucity of CVD cohort studies that integrate earlier lifecourse stages (eg, infancy to adolescence) with the adult studies.…”
Section: Discussionmentioning
confidence: 99%
“…As stated previously, two different versions of ActiGraph monitors were used in two different wear locations (AM-7164 worn on the hip in 2003-2004 and 2005-2006 cycles and GT3X+ worn on the wrist in 2011-2012 and 2012-2014 cycles) (22). Step data have not been released from the NHANES data set, but there is increasing interest in health outcomes related to steps per day (6)(7)(8). In our systematic literature review, we could not locate a study that conducted a direct comparison between the hip-worn AM-7164 and GT3X worn on the wrist.…”
Section: Discussionmentioning
confidence: 99%
“…Both researchers and the public are interested in steps because they are more easily understood than other units representing the volume of physical activity, such as minutes of moderate-to-vigorous physical activity or total activity counts. Moreover, steps per day are inversely related to adiposity (3), metabolic disease (i.e., type 2 diabetes) (4,5), cardiovascular events (6), and all-cause mortality (7,8).…”
mentioning
confidence: 99%
“…Paluch and colleagues conducted an extensive meta‐analysis of published and unpublished prospective cohort data related to daily steps and cardiovascular disease (CVD) 7 . Steps were counted using one of 5 waist‐worn devices and averaged activity over 3 to 7 days.…”
Section: How Many Daily Steps Are Needed For Health?mentioning
confidence: 99%